Thomism’s Ontology of Evolution: Tabaczek’s Account - Dumsday, Travis (Theology and science, 2025)
Fr. Tabaczek's Theistic Evolution constitutes a significant contribution to the Thomistic (and more broadly Neo-Aristotelian / Neo-Scholastic) literature on the metaphysics of biological evolution. The text engages with multiple contested issues in this arena, including natural-kind essentialism, substance ontology, individuation, and the ontological bases of biologists’ taxonomical practices. In this brief response piece, I seek to provide a concise overview and assessment of some of Fr. Tabaczek's core claims and arguments on these matters.